Analisa Potensi Dan Tantangan Ekspor Komoditas Kopi Indonesia Ke Malaysia - Daspar; Erlin Ayu Widiya; Nilam Ayuningtyas; Niken Wahyuningrum; Rina Sonia (Jurnal Ekonomi dan Bisnis Digital, 2024)
International trade is one of the main components in driving a country's economy, providing opportunities and opportunities for sustainable growth. Exports and imports are an inseparable part of international trade, where exports have an important role in increasing state income and providing benefits such as increasing foreign exchange reserves, expanding employment opportunities, and a means to market domestic products. Indonesia, with its natural resource potential, especially in the plantation industry such as coffee, plays a significant role in international trade. Indonesia's high coffee production makes it one of the largest producers in the world, with exports reaching countries such as the United States, Germany and Japan. However, the Indonesian coffee industry is also faced with various challenges, including changes in consumer demand, the impact of climate change, and competition with other coffee producing countries such as Vietnam and India. To optimize Indonesia's coffee export potential, more aggressive promotional and marketing efforts are needed, as well as attention to environmental aspects and consumer preferences.